An EPS-derived carbon-nitrogen fragment-anchored Cu3P / Ni2P heterojunction electrocatalyst as well as a preparation method and application thereof
By introducing EPS-derived carbon and nitrogen fragments into the Cu3P/Ni2P heterojunction interface and constructing CP covalent bonds, the problem of interface reconstruction of the catalyst under electrochemical conditions was solved, achieving high activity, high selectivity and high stability of electrocatalytic performance, and improving the efficiency of PET plastic upgrading and recycling coupled with hydrogen production.
Patent Information
- Application Number
- CN202611393802.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-11-03
AI Technical Summary
Existing transition metal phosphide catalysts suffer from interfacial reconstruction under electrochemical conditions, resulting in insufficient activity and stability, making it difficult to achieve highly active, selective, and stable electrocatalytic oxidation reactions.
By in-situ introducing EPS-derived carbon and nitrogen fragments at the Cu3P/Ni2P heterojunction interface, CP covalent bonds are constructed to form a carbon and nitrogen fragment anchoring structure, thereby regulating the electronic structure and enhancing the adsorption capacity for reaction intermediates.
The structure stability and selectivity of the electrocatalyst were significantly improved, giving it high activity, high selectivity and high stability in the ethylene glycol oxidation reaction. The Faraday efficiency of ethylene glycol to formate reached 98.5%, realizing the efficient conversion of PET plastic upgrading and recycling coupled with hydrogen production.
Smart Images

Figure CN123027618A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrocatalytic materials technology, specifically to an EPS-derived carbon and nitrogen fragment anchored Cu3P / Ni2P heterojunction electrocatalyst, its preparation method, and its application. Background Technology
[0002] With the continuous accumulation of plastic waste and the ever-growing demand for green hydrogen, the development of synergistic technologies that combine environmental governance and clean energy production is of great significance. Electrochemical plastic upgrading and recycling can oxidize plastic-derived ethylene glycol (EG) into high-value chemicals, while simultaneously coupling the cathodic hydrogen evolution reaction (HER) to replace the energy-intensive oxygen evolution reaction (OER). Currently, the commonly used catalysts for ethylene glycol oxidation (EGOR) are precious metals such as Pt and Pd, which are costly and have limited selectivity. Transition metal phosphides (such as Cu3P and Ni2P) have attracted attention due to their good conductivity and tunable electronic structure, but their single-component catalytic activity is limited, and they are prone to interfacial reconstruction under electrochemical conditions, resulting in insufficient stability. Constructing Cu3P / Ni2P heterojunctions can optimize the interfacial electronic structure, but traditional synthesis methods make it difficult to achieve precise control of the interface at the atomic scale, resulting in a trade-off between activity and stability.
[0003] Therefore, it is of great significance to develop an electrocatalytic material that combines high activity, high selectivity and high stability. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide an EPS-derived carbon and nitrogen fragment anchored Cu3P / Ni2P heterojunction electrocatalyst, its preparation method, and its application. This invention introduces EPS-derived carbon and nitrogen fragments in situ at the Cu3P / Ni2P heterojunction interface to construct CP covalent bonds, forming a carbon and nitrogen fragment anchored structure. This significantly improves the structural stability and catalytic selectivity of the electrocatalyst, enabling it to exhibit high activity, high selectivity, and high stability in electrocatalytic oxidation reactions.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a Cu3P / Ni2P heterojunction electrocatalyst anchored with EPS-derived carbon and nitrogen fragments, comprising a conductive substrate and a Cu3P / Ni2P heterojunction nanoarray grown on the conductive substrate. Carbon and nitrogen fragments are anchored at the heterojunction interface of the Cu3P / Ni2P heterojunction nanoarray via CP covalent bonds, and the carbon and nitrogen fragments are derived from bacterial extracellular polymers (EPS).
[0006] Preferably, the Cu3P / Ni2P heterojunction nanoarray is composed of three-dimensional nanoclusters, which are formed by stacking nanosheets, and the thickness of the nanosheets is 20~50nm.
[0007] Preferably, the intensity ratio of the D band to the G band in the Raman spectrum of the carbon-nitrogen fragment is I. D / I G The value is 0.8~1.2.
[0008] This invention also provides a method for preparing the Cu3P / Ni2P heterojunction electrocatalyst described above, comprising the following steps: Place the conductive substrate in a Cu-containing environment 2+ and Ni 2+ Electrodeposition was performed on an aqueous solution of bacterial extracellular polymer to obtain a conductive substrate with a Cu(OH)2 / Ni(OH)2 precursor nanoarray grown on it. The conductive substrate on which the Cu(OH)2 / Ni(OH)2 precursor nanoarray is grown is subjected to heat treatment with a phosphorus source to obtain the Cu3P / Ni2P heterojunction electrocatalyst.
[0009] Preferably, the Cu-containing 2+ and Ni 2+ The volume fraction of bacterial extracellular polymers in the aqueous solution is 5-30%.
[0010] Preferably, the Cu-containing 2+ and Ni 2+ Cu in bacterial extracellular polymeric aqueous solution 2+ Concentration of 1~5 mmol / L, Ni 2+ The concentration is 1~5 mmol / L.
[0011] Preferably, the electrodeposition treatment is performed at a potential of -1.5 to -1.0 V vs. Ag / AgCl, and the electrodeposition treatment time is 100 to 500 s.
[0012] Preferably, the phosphorus source includes one or more of sodium hypophosphite, sodium phosphite, and sodium phosphate; the mass ratio of the phosphorus source to the Cu(OH)2 / Ni(OH)2 precursor nanoarray in the conductive substrate on which the Cu(OH)2 / Ni(OH)2 precursor nanoarray is grown is 1:1 to 5:1.
[0013] Preferably, the heat treatment temperature is 300~400℃ and the holding time is 1~4h.
[0014] This invention also provides the application of the Cu3P / Ni2P heterojunction electrocatalyst described in the above technical solution or the Cu3P / Ni2P heterojunction electrocatalyst prepared by the above preparation method in the coupled hydrogen production of PET plastic upgrading and recycling, wherein the Cu3P / Ni2P heterojunction electrocatalyst is the anode and / or cathode.
[0015] This invention provides an EPS-derived carbon and nitrogen fragment anchored Cu3P / Ni2P heterojunction electrocatalyst, comprising a conductive substrate and a Cu3P / Ni2P heterojunction nanoarray grown on the conductive substrate. Carbon and nitrogen fragments are anchored at the heterojunction interface of the Cu3P / Ni2P heterojunction nanoarray via CP covalent bonds, and the carbon and nitrogen fragments are derived from bacterial extracellular polymers.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention utilizes the growth of Cu3P / Ni2P heterojunction nanoarrays on a conductive substrate. The Cu3P / Ni2P heterojunction nanoarray structure not only possesses abundant specific surface area and highly exposed active sites, but also provides excellent electron / ion transport channels and structural stability for electrocatalytic reactions, thereby significantly improving the electrochemical performance and lifespan of the catalyst. By in-situ introducing EPS-derived carbon and nitrogen fragments at the Cu3P / Ni2P heterojunction interface, CP covalent bonds are constructed, forming a carbon and nitrogen fragment anchoring structure. These carbon and nitrogen fragments act as electron acceptors, directionally attracting electrons from Cu and Ni sites, inducing charge redistribution, resulting in electron-deficient metal sites and electron-rich carbon and nitrogen regions. Simultaneously, this regulates and generates spatial heteroelectrostatic potential, thereby enhancing the adsorption capacity for reaction intermediates, improving the selectivity and efficiency of the catalytic reaction, and enabling the electrocatalyst to exhibit high activity, high selectivity, and long-term operational stability during the reaction.
[0017] This invention also provides the application of the Cu3P / Ni2P heterojunction electrocatalyst described in the above technical solution or the Cu3P / Ni2P heterojunction electrocatalyst prepared by the above preparation method in the coupling hydrogen production of PET plastic upgrading and recycling. This invention achieves precise control of the electronic structure of the Cu3P / Ni2P heterojunction interface through the covalently anchored carbon and nitrogen fragments of the CP bond, switching the ethylene glycol oxidation reaction pathway from the traditional glycolic acid-mediated pathway to the glyoxal-mediated pathway, so that the Faraday efficiency of selectively breaking the C-C bond to generate formate is as high as 98.5%, realizing the highly selective conversion of PET hydrolysis product ethylene glycol into high-value chemical formate. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the catalytic reaction mechanism of the present invention; Figure 2 In the figures, a and b are scanning electron microscope (SEM) images of bio2-Cu3P / Ni2P in Example 1, and c and d are scanning electron microscope (SEM) images of Cu3P / Ni2P in Comparative Example 3. Figure 3In Figure a, we have a transmission electron microscope (TEM) image of bio2-Cu3P / Ni2P from Example 1, and we have high-resolution transmission electron microscope (HRTEM) images of bio2-Cu3P / Ni2P from Example 1. Figure 4 The image shows the elemental energy dispersive spectroscopy (EDS) mapping of bio2-Cu3P / Ni2P in Example 1. From left to right, the images are the HAADF image and the distribution maps of Cu, Ni, and P elements. Figure 5 The X-ray diffraction (XRD) spectra of bio2-Cu3P / Ni2P in Example 1 and Cu3P / Ni2P in Comparative Example 3 are shown. Figure 6 The image shows a high-resolution comparison of X-ray photoelectron spectroscopy (XPS) of bio2-Cu3P / Ni2P in Example 1 and Cu3P / Ni2P in Comparative Example 3. a is the Cu 2p spectrum, b is the Ni 2p spectrum, and c is the N 1s spectrum. Figure 7 The Fourier transform infrared (FTIR) spectra of bio2-Cu3P / Ni2P in Example 1 and Cu3P / Ni2P in Comparative Example 3 are shown in the figure. Figure 8 In Figure a, the Raman spectrum of bio2-Cu3P / Ni2P in Example 1 is shown, and in Figure b, the Raman surface distribution of bio2-Cu3P / Ni2P in Example 1 is shown. Figure 9 In the figure, a is the HER polarization curve of the samples in Examples 1-2 and Comparative Example 3, b is the electrochemical impedance spectroscopy (EIS) Nyquist plot of the samples in Examples 1-2 and Comparative Example 3, and c is the EGOR polarization curve of the samples in Examples 1-2 and Comparative Example 3. Figure 10 In the figure, a represents the HER polarization curves of Pd / C and Pt / C in Examples 1, Comparative Examples 1-3, and Comparative Example 4; b represents the Tafel slope of Pd / C and Pt / C in Examples 1, Comparative Examples 1-3, and Comparative Example 4; c represents the double-layer capacitance (Cdl) of the samples in Examples 1 and Comparative Examples 1-4; and d represents the stability curve of Pt / C in Examples 1, Comparative Example 3, and Comparative Example 4. Figure 11 In Figure a, the EGOR polarization curves of Pd / C and RuO2 in Examples 1, Comparative Examples 1-3 and Comparative Example 4 are shown; in Figure b, the Faraday efficiency and product yield of the sample in Example 1 are shown; and in Figure c, the cycle stability test results of the sample in Example 1 are shown. Figure 12 In Figure a, the in-situ infrared spectrum of bio2-Cu3P / Ni2P in Example 1 is shown, and in Figure b, the in-situ infrared spectrum of Cu3P / Ni2P in Comparative Example 3 is shown. Figure 13 In the diagram, a is a left view of the theoretical model structure of Cu3P / Ni2P in Comparative Example 3, b is a top view of the theoretical model structure of Cu3P / Ni2P in Comparative Example 3, c is a left view of the theoretical model structure of the sample in Example 1, and d is a top view of the theoretical model structure of the sample in Example 1. Figure 14 In Figure a, it is a schematic diagram of the two pathways of the ethylene glycol oxidation reaction; in Figure b, it is a free energy step diagram of the two pathways on bio2-Cu3P / Ni2P; and in Figure c, it is a free energy step diagram of the two pathways on Cu3P / Ni2P. Figure 15 In Figure 2, a is the linear sweep voltammetry (LSV) curve in different PET hydrolysates in test example 2, b is a schematic diagram of the solar-driven PET upgrade and recycling coupled hydrogen production system, c is the FTIR spectrum of recovered terephthalic acid, and d is the FTIR spectrum of recovered potassium diformate. Detailed Implementation
[0019] This invention provides an EPS-derived carbon and nitrogen fragment anchored Cu3P / Ni2P heterojunction electrocatalyst, comprising a conductive substrate and a Cu3P / Ni2P heterojunction nanoarray grown on the conductive substrate. Carbon and nitrogen fragments are anchored at the heterojunction interface of the Cu3P / Ni2P heterojunction nanoarray via CP covalent bonds, and the carbon and nitrogen fragments are derived from bacterial extracellular polymers.
[0020] In this invention, the Cu3P / Ni2P heterojunction nanoarray is preferably composed of three-dimensional nanoclusters, which are preferably formed by stacking nanosheets. The thickness of the nanosheets is preferably 20-50 nm. The Cu3P / Ni2P heterojunction nanoarray structure not only has abundant specific surface area and highly exposed active sites, but also provides good electron / ion transport channels and structural stability for the electrocatalytic reaction process, thereby significantly improving the electrochemical performance and service life of the catalyst.
[0021] In this invention, the intensity ratio of the D band to the G band in the Raman spectrum of the carbon-nitrogen fragment is I. D / I G The preferred value is 0.8~1.2, specifically 0.9, 0.92 or 1.0. The carbon-nitrogen fragments are preferably disordered carbon structures. By introducing EPS-derived carbon-nitrogen fragments in situ at the Cu3P / Ni2P heterojunction interface, CP covalent bonds are constructed to form a carbon-nitrogen fragment anchoring structure. The carbon-nitrogen fragments act as electron acceptors, attracting electrons directionally from Cu and Ni sites, inducing charge redistribution, making the metal sites electron-deficient and the carbon-nitrogen regions electron-rich. At the same time, it regulates and generates spatial heteroelectrostatic potential, thereby enhancing the adsorption capacity for reaction intermediates and improving the selectivity and efficiency of the catalytic reaction.
[0022] In this invention, the conductive substrate preferably comprises nickel foam or carbon cloth, and the size of the conductive substrate is preferably 2cm × 0.7cm.
[0023] This invention also provides a method for preparing the Cu3P / Ni2P heterojunction electrocatalyst described in the above technical solution, comprising the following steps: Place the conductive substrate in a Cu-containing environment 2+ and Ni 2+ Electrodeposition was performed on an aqueous solution of bacterial extracellular polymer to obtain a conductive substrate with a Cu(OH)2 / Ni(OH)2 precursor nanoarray grown on it. The conductive substrate on which the Cu(OH)2 / Ni(OH)2 precursor nanoarray is grown is subjected to heat treatment with a phosphorus source to obtain the Cu3P / Ni2P heterojunction electrocatalyst.
[0024] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.
[0025] This invention places a conductive substrate in a Cu-containing environment. 2+ and Ni 2+ Electrodeposition was performed on an aqueous solution of bacterial extracellular polymer to obtain a conductive substrate with a Cu(OH)2 / Ni(OH)2 precursor nanoarray.
[0026] In this invention, the conductive substrate is preferably pretreated before use. The pretreatment preferably involves ultrasonically cleaning the conductive substrate in acetone, dilute hydrochloric acid, and anhydrous ethanol in sequence. The concentration of the dilute hydrochloric acid is preferably 3 mol / L, and the ultrasonic cleaning time for acetone, dilute hydrochloric acid, and anhydrous ethanol is preferably 15 min. After cleaning, the substrate is dried for later use. The drying time is preferably 5 to 15 min, and the temperature is preferably 40 to 60°C. The pretreatment can remove oxides and impurities.
[0027] In this invention, it is preferable to first prepare an aqueous solution of bacterial extracellular polymeric substances (EPS aqueous solution) before performing the electrodeposition treatment.
[0028] In this invention, the preferred method for preparing the EPS aqueous solution includes: inoculating a bacterial strain into LB medium and culturing with shaking, centrifuging to collect the supernatant, and obtaining the EPS aqueous solution.
[0029] In this invention, the role of bacterial extracellular polymers is to regulate the morphology of precursors during electrodeposition and to form carbon and nitrogen fragments anchored at the heterojunction interface in situ as a carbon and nitrogen source during subsequent heat treatment. Therefore, any bacterial strain capable of secreting nitrogen-containing extracellular polymers can be used in this invention, and it is not limited to a specific species. Those skilled in the art can select suitable EPS-producing strains according to actual needs. In one embodiment of this invention, the bacterial strain is preferably... Pseudomonas azotoformans The strain is preferably the strain published in CN112940964A, entitled "A microbial agent for improving rocky desertification soil in karst valley areas and its preparation and application".
[0030] In this invention, the preferred temperature for the oscillation culture is 28°C, the preferred rotation speed is 130 rpm, and the preferred time is 24 h. The preferred rotation speed for the centrifugation is 6000~8000 rpm, and the preferred time is 10~15 min.
[0031] In this invention, the Cu-containing 2+ and Ni 2+ The preferred method for preparing the aqueous solution of bacterial extracellular polymeric substances (EPS) is as follows: copper salt and nickel salt are dissolved in deionized water, and then the EPS aqueous solution is added, so that the EPS contains Cu 2+ and Ni 2+ The volume fraction of the bacterial extracellular polymeric substance in the aqueous solution is 5%~30%, specifically 8%, 10%, 15%, 20% or 25%, wherein the Cu-containing... 2+ and Ni 2+ Cu in bacterial extracellular polymeric aqueous solution 2+ The preferred concentration is 1-5 mmol / L, wherein the Cu-containing 2+ and Ni 2+ Ni in bacterial extracellular polymeric aqueous solution 2+ The concentration is 1~5 mmol / L, and the copper salt preferably includes Cu(NO3)2·3H2O, and the nickel salt preferably includes Ni(NO3)2·6H2O.
[0032] In this invention, the conductive substrate and the Cu-containing substrate 2+ and Ni 2+ The preferred ratio of bacterial extracellular polymeric acid aqueous solution to water is 10~30 mL / cm³. 2 .
[0033] In this invention, the electrodeposition process is preferably performed using a three-electrode system: a pretreated conductive substrate as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode. The electrodeposition potential relative to the Ag / AgCl reference electrode is preferably -1.5V to -1.0V, specifically -1.4, -1.3, -1.2, or -1.1V. The electrodeposition time is preferably 100 to 500 s, specifically 150, 200, 300, 350, 400, or 450 s. Under negative potential driving, the Cu-containing... 2+ and Ni 2+ Cu in bacterial extracellular polymeric aqueous solution 2+ and Ni 2+A reduction reaction occurs on the surface of the conductive substrate, reacting with OH- in the electrolyte. - Combined with the formation of Cu(OH)₂ and Ni(OH)₂ precipitates, the carboxyl and hydroxyl functional groups in EPS are adsorbed onto the surface of newly formed crystal nuclei through coordination, regulating the growth direction of the crystal nuclei, inhibiting particle aggregation, and promoting the formation of nanosheet structures. The functional groups in EPS interact with Cu... 2+ Ni 2+ The coordination effect of EPS controls the release and reduction rate of metal ions, promotes the formation and ordered self-assembly of nanosheet hydroxides, and not only modulates the morphology of the precursor, but also provides an organic precursor for the subsequent anchoring of carbon and nitrogen fragments.
[0034] In this invention, after the electrodeposition treatment, the obtained substrate is preferably rinsed with deionized water and then dried at 40°C to obtain a conductive substrate with Cu(OH)2 and Ni(OH)2 precursor nanoarrays grown on it.
[0035] After obtaining a conductive substrate with Cu(OH)2 and Ni(OH)2 precursor nanoarrays grown on it, the present invention heat-treats the conductive substrate with Cu(OH)2 and Ni(OH)2 precursor nanoarrays grown on it with a phosphorus source to obtain the Cu3P / Ni2P heterojunction electrocatalyst.
[0036] In this invention, the phosphorus source preferably includes one or more of sodium hypophosphite, sodium phosphite, and sodium phosphate. The mass ratio of the phosphorus source to the Cu(OH)2 / Ni(OH)2 precursor nanoarray in the conductive substrate on which Cu(OH)2 and Ni(OH)2 precursor nanoarrays are grown is preferably 1:1 to 5:1, specifically 2:1, 3:1, or 4:1.
[0037] In this invention, the heat treatment temperature is preferably 300~400℃, specifically 320, 340, 350 or 380℃, and preferably the temperature is increased from room temperature to the heat treatment temperature at a heating rate of 2~10℃ / min, specifically 3, 5 or 8℃ / min. The heat treatment holding time is preferably 1~4h.
[0038] In this invention, the heat treatment is preferably carried out in an inert gas atmosphere, preferably nitrogen, argon or helium.
[0039] In this invention, the heat treatment is preferably carried out in a tube furnace. The conductive substrate with Cu(OH)₂ and Ni(OH)₂ precursor nanoarrays is placed downstream of the tube furnace, and the phosphorus source is placed upstream of the tube furnace. The distance between the phosphorus source and the conductive substrate with Cu(OH)₂ and Ni(OH)₂ precursor nanoarrays is preferably 2-8 cm. The phosphorus source decomposes at high temperature to generate PH₃ active phosphorus species, which react with hydroxides to form metal phosphides. Simultaneously, the carbon and nitrogen fragments derived from EPS are not completely removed but are connected to the phosphide lattice through CP covalent bonds, forming a stable covalently anchored structure. This phosphating process simultaneously achieves the formation of heterojunctions and the covalent anchoring of carbon and nitrogen fragments, simplifying the synthesis steps and ensuring the stability of the interface structure. The carbon and nitrogen-containing organic components in EPS undergo carbonization at high temperature, forming a graphite-like carbon and nitrogen structure. At the same time, the active phosphorus species generated by phosphating react with carbon atoms at the edges of the carbon and nitrogen fragments to form CP covalent bonds, firmly fixing the carbon and nitrogen fragments to the phosphide surface.
[0040] In this invention, the product obtained after heat treatment is preferably naturally cooled to room temperature to obtain the Cu3P / Ni2P heterojunction electrocatalyst.
[0041] This invention also provides the application of the Cu3P / Ni2P heterojunction electrocatalyst described in the above technical solution or the Cu3P / Ni2P heterojunction electrocatalyst prepared by the above preparation method in the coupled hydrogen production of PET plastic upgrading and recycling, wherein the Cu3P / Ni2P heterojunction electrocatalyst is the anode and / or cathode.
[0042] In this invention, the preferred method for upgrading and recycling PET plastics to produce hydrogen includes the following steps: alkaline hydrolysis of PET plastics to obtain an electrolyte, and electrolysis in an electrolytic cell using the Cu3P / Ni2P heterojunction electrocatalyst as the anode and / or cathode.
[0043] In this invention, when the Cu3P / Ni2P heterojunction electrocatalyst is the anode, the cathode is preferably a Pt electrode; when the Cu3P / Ni2P heterojunction electrocatalyst is the cathode, the anode is preferably a Pt electrode.
[0044] In this invention, the electrolyte preferably comprises a mixed solution containing ethylene glycol and terephthalate.
[0045] In this invention, the alkaline solution for alkaline hydrolysis preferably includes a KOH solution, the concentration of the KOH solution is preferably 0.5~1 mol / L, the alkaline hydrolysis time is preferably 5~100 h, and the temperature is preferably 20~30℃.
[0046] In this invention, an ethylene glycol oxidation reaction occurs at the anode to generate formate, and a hydrogen evolution reaction occurs at the cathode to generate hydrogen gas.
[0047] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0048] Example 1 Commercially available nickel foam with dimensions of 2cm × 0.7cm was selected as the conductive substrate and ultrasonically cleaned in acetone, 3mol / L dilute hydrochloric acid, and anhydrous ethanol for 15min in sequence to obtain pretreated nickel foam, which was then dried for later use. Will Pseudomonas azotoformans The strain was inoculated into LB medium and cultured at 28°C and 130 rpm for 24 h with shaking. The supernatant was collected by centrifugation as EPS stock solution. Prepare 20 mL of EPS aqueous solution containing 1 mmol / L Cu(NO3)2·3H2O and 1 mmol / L Ni(NO3)2·6H2O, with a volume fraction of 10% EPS in the EPS aqueous solution. Stir magnetically for 10 min. Vertically immerse the pretreated nickel foam into the EPS aqueous solution. Using a three-electrode system (nickel foam as the working electrode, platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode), electrodeposit for 300 s at a potential of -1.5 V vs. Ag / AgCl. After deposition, remove the nickel foam, rinse with deionized water, and dry at 40 °C to obtain a conductive substrate with Cu(OH)2 / Ni(OH)2 precursor grown on it. 0.1 g of sodium hypophosphite was placed upstream of a tube furnace, and a conductive substrate with Cu(OH)2 / Ni(OH)2 precursors was placed 4 cm downstream. Under a nitrogen atmosphere, the temperature was increased to 300 °C at 5 °C / min, held for 2 h, and then naturally cooled to room temperature to obtain a Cu3P / Ni2P heterojunction electrocatalyst, denoted as bio2-Cu3P / Ni2P.
[0049] Example 2 Similar to Example 1, the only difference is that the volume fraction of EPS in the EPS aqueous solution is 5% and 15%, respectively, and the resulting Cu3P / Ni2P heterojunction catalysts are denoted as bio1-Cu3P / Ni2P and bio3-Cu3P / Ni2P, respectively.
[0050] Comparative Example 1 Following the method of Example 1, the only difference is that Ni(NO3)2·6H2O and EPS are not added, and only 5 mmol / L Cu(NO3)2·3H2O is contained to obtain a single-component Cu3P catalyst.
[0051] Comparative Example 2 Similar to Example 1, except that Cu(NO3)2·3H2O and EPS were not added, and only 5 mmol / L Ni(NO3)2·6H2O was added to obtain a single-component Ni2P catalyst.
[0052] Comparative Example 3 Similar to Example 1, except that EPS was not added, and only 5 mmol / L Cu(NO3)2·3H2O and 5 mmol / L Ni(NO3)2·6H2O were added to obtain Cu3P / Ni2P catalyst without added EPS, which is denoted as Cu3P / Ni2P catalyst.
[0053] Comparative Example 4 10 mg of commercially available Pd / C (Shanghai Adamas Reagent Co., Ltd., Pd accounts for 10% of the total catalyst mass), RuO2 (Shanghai Adamas Reagent Co., Ltd., RuO2 purity is 99.95%), and Pt / C (Shanghai Adamas Reagent Co., Ltd., Pt accounts for 10% of the total catalyst mass) catalysts were dispersed in 0.2 mL of ethanol / 0.7 mL of water mixed solvent, respectively. 100 μL of 0.5% Nafion solution was added, and the mixture was ultrasonically dispersed to form a uniform ink. 100 μL of this ink was then drop-coated onto the surface of pretreated nickel foam (0.5 cm²). 2 After drying at room temperature, Pd / C and Pt / C working electrodes were obtained with a catalyst loading of 2 mg / cm³. 2 .
[0054] Figure 1 This is a schematic diagram of the catalytic reaction mechanism of the present invention. As can be seen from the figure, the carbon-nitrogen fragments derived from EPS are anchored at the Cu3P / Ni2P heterointerface. This bio-interface locking effect causes the oxidation pathway of PET-derived ethylene glycol to change from the formation of glycolate to the CC cleavage pathway via aldehyde / glyoxal intermediate, thereby achieving efficient coupling between the selective electrosynthesis of formate and the hydrogen evolution reaction.
[0055] Figure 2 In Figures a and b, we see scanning electron microscope (SEM) images of bio2-Cu3P / Ni2P from Example 1, and c and d, we see scanning electron microscope (SEM) images of Cu3P / Ni2P from Comparative Example 3. The bio2-Cu3P / Ni2P electrocatalyst exhibits a three-dimensional nanocluster structure formed by stacked nanosheets. The Cu3P / Ni2P electrocatalyst is in the form of aggregated particles with irregular morphology. The results indicate that the introduction of EPS significantly modulates the material morphology, forming an open structure that is conducive to mass transport and exposure of active sites.
[0056] Figure 3In Figure a, the transmission electron microscope (TEM) image of bio2-Cu3P / Ni2P in Example 1 is shown, and the high-resolution transmission electron microscope (HRTEM) images of bio2-Cu3P / Ni2P in Example 1 are shown. Figure 3 In the image, nanosheets are stacked together to form nanocluster structures. Figure 2 The image in b shows clear lattice fringes, with interplanar spacings of 0.276 nm and 0.221 nm corresponding to the (300) plane of Cu3P and the (111) plane of Ni2P, respectively, confirming the formation of a Cu3P / Ni2P heterojunction. Figure 3 Significant lattice distortion was observed in the heterogeneous interface region of the middle C, which was attributed to local atomic rearrangement caused by the covalent anchoring of carbon and nitrogen fragments derived from EPS.
[0057] Figure 4 The image shows the elemental energy dispersive spectroscopy (EDS) mapping of bio2-Cu3P / Ni2P in Example 1. From left to right, the images are the HAADF image and the distribution maps of Cu, Ni, and P elements. The image shows that each element is uniformly distributed on the surface of the material, confirming the successful synthesis of the catalyst.
[0058] Figure 5 The X-ray diffraction (XRD) spectra of bio2-Cu3P / Ni2P in Example 1 and Cu3P / Ni2P in Comparative Example 3 are shown; both samples show characteristic diffraction peaks of Cu3P (PDF#27-1120) and Ni2P (PDF#03-0953).
[0059] Figure 6 The image shows a high-resolution comparison of X-ray photoelectron spectroscopy (XPS) spectra of bio2-Cu3P / Ni2P from Example 1 and Cu3P / Ni2P from Comparative Example 3. a is the Cu 2p spectrum, b is the Ni 2p spectrum, and c is the N 1s spectrum. It can be seen that the Cu 2p 3 / 2 peak in bio2-Cu3P / Ni2P shifted from 932.6 eV to 932.9 eV, and the Ni 2p 3 / 2 peak shifted from 855.8 eV to 856.5 eV. Both shifted towards higher binding energies (Cu shifted 0.3 eV, Ni shifted 0.7 eV), indicating a decrease in electron density at the metal sites. The carbon and nitrogen fragments derived from EPS act as electron acceptors, attracting electrons. A CN characteristic peak of 398.7 eV appears in bio2-Cu3P / Ni2P, while this signal is absent in the Cu3P / Ni2P sample without added EPS, confirming that nitrogen originates from EPS and is retained in the catalyst.
[0060] Figure 7 This is a comparison of the Fourier transform infrared (FTIR) spectra of bio2-Cu3P / Ni2P from Example 1 and Cu3P / Ni2P from Comparative Example 3; bio2-Cu3P / Ni2P at 1117 cm⁻¹ -1The presence of a characteristic absorption peak for CP bonds, which was absent in Cu3P / Ni2P samples without added EPS, confirms that the EPS-derived carbon and nitrogen fragments are connected to the metal phosphide lattice via CP covalent bonds, forming a stable chemical anchor.
[0061] Figure 8 In Figure a, the Raman spectrum of bio2-Cu3P / Ni2P in Example 1 is shown, and in Figure b, the Raman surface distribution of bio2-Cu3P / Ni2P in Example 1 is shown. Figure 8 The middle a shows that bio2-Cu3P / Ni2P at 1170 cm⁻¹ -1 (D belt) and 1550cm -1 (G band) shows characteristic peaks of carbon materials, I D / I G A ratio of 0.92 indicates that the carbon and nitrogen fragments exhibit a highly disordered structure. Figure 8 Figure b shows the intensity surface distribution of the G band, which indicates that the carbon signal is spatially heterogeneous on the catalyst surface, suggesting that EPS-derived carbon and nitrogen fragments are preferentially anchored in specific regions.
[0062] Test Example 1 This test example uses a three-electrode system for electrochemical testing on a CHI 760E electrochemical workstation. The bio2-Cu3P / Ni2P electrode obtained in Example 1 was used as the working electrode, a platinum wire as the counter electrode, and an Hg / HgO (1 mol / L KOH) electrode as the reference electrode. HER testing was performed in a 1.0 mol / L KOH electrolyte; EGOR testing was performed in a 1.0 mol / L KOH electrolyte containing 0.5 mol / L ethylene glycol. All test potentials were converted to the reversible hydrogen electrode (RHE) potential based on the Nernst equation: ERHE = EHg / HgO + 0.098 + 0.059 × pH. Linear sweep voltammetry (LSV) was performed at a scan rate of 5 mV / s. Electrochemical impedance spectroscopy (EIS) was performed in the frequency range of 100 kHz to 0.01 Hz, with an AC perturbation voltage amplitude of 5 mV. Stability testing was performed using a galvanostatic method with a current density of 100 mA / cm². 2 .
[0063] Figure 9 In the figure, a is the HER polarization curve of the samples in Examples 1-2 and Comparative Example 3, b is the electrochemical impedance spectroscopy (EIS) Nyquist plot of the samples in Examples 1-2 and Comparative Example 3, and c is the EGOR polarization curve of the samples in Examples 1-2 and Comparative Example 3. Figure 9 The data in section a shows that bio2-Cu3P / Ni2P is at 100 mA / cm 2 The overpotential is lowest at current density (148mV). Figure 9In the diagram, b indicates that bio2-Cu3P / Ni2P exhibits the smallest charge transfer resistance. Figure 9 The C-type display shows that bio2-Cu3P / Ni2P reaches 100 mA / cm². 2 The required potential is the lowest (1.329V). The results show that an appropriate concentration of EPS can effectively regulate the heterojunction interface structure and optimize electron transfer performance. Among them, 10% volume fraction is the optimal concentration of EPS in this invention. When the concentration is too low, the carbon and nitrogen fragments are not anchored enough, making it difficult to effectively regulate the electronic structure. When the concentration is too high, the carbon and nitrogen fragments accumulate excessively, which may hinder the exposure of active sites and cause a decline in performance.
[0064] Figure 10 In the figure, a represents the HER polarization curves of Pd / C and Pt / C in Examples 1, Comparative Examples 1-3, and Comparative Example 4; b represents the Tafel slope of Pd / C and Pt / C in Examples 1, Comparative Examples 1-3, and Comparative Example 4; c represents the double-layer capacitance (Cdl) of the samples in Examples 1 and Comparative Examples 1-4; and d represents the stability curve of Pt / C in Examples 1, Comparative Example 3, and Comparative Example 4. Figure 10 As shown in Figure a, bio2-Cu3P / Ni2P at 100 mA / cm 2 The voltage was 148 mV, significantly lower than that of the control sample: Cu3P / Ni2P (287 mV @ 100 mA / cm). 2 Cu3P (391mV@100mA / cm) 2 Ni2P (337mV@100mA / cm) 2 Pd / C (243mV@100mA / cm) 2 Pt / C (224mV@100mA / cm) 2 ), Figure 10 The figure shows that the Tafel slope of bio2-Cu3P / Ni2P is 51.7 mV·dec. -1 The value was lower than 149.1 mV·dec for the Cu3P / Ni2P sample without EPS addition. -1 This indicates that the reaction kinetics are superior. Figure 10 The Cdl of bio2-Cu3P / Ni2P is shown to be 12.3 mF / cm. 2 The value is higher than the 6.2 mF / cm of the Cu3P / Ni2P sample without EPS addition. 2 Consistent with the porous structure observed by SEM Figure 10 Mid-d stability tests show that bio2-Cu3P / Ni2P maintains stability at 100 mA / cm². 2 After 100 hours of stable operation, the potential did not increase significantly; while the Cu3P / Ni2P sample without EPS showed a potential increase of 36mV in the same time period.
[0065] Figure 11 In Figure a, the EGOR polarization curves of Pd / C and RuO2 in Examples 1, Comparative Examples 1-3 and Comparative Example 4 are shown; in Figure b, the Faraday efficiency and product yield of the sample in Example 1 are shown; and in Figure c, the cycle stability test results of the sample in Example 1 are shown. Figure 11 The data in Figure a shows that bio2-Cu3P / Ni2P reaches 100 mA / cm². 2 The required potential is 1.322V, which is lower than that of Cu3P / Ni2P without EPS (1.430V), Cu3P (1.465V), Ni2P (1.459V), Pd / C (1.417V), and RuO2 (1.458V). Figure 11 The β-Faraday efficiency test showed that bio2-Cu3P / Ni2P achieved a formate Faraday efficiency of 98.5% under 1.55V vs. RHE conditions, and the formate yield remained stable at 2.13 mmol·cm³ during 10 hours of continuous operation. -2 ·h -1 , Figure 11 Cyclic stability tests showed that after 10 potential cycles, the formate selectivity remained above 90%.
[0066] Figure 12 Image a shows the in-situ infrared spectrum of bio2-Cu3P / Ni2P from Example 1, and image b shows the in-situ infrared spectrum of Cu3P / Ni2P from Comparative Example 3; showing that the Cu3P / Ni2P sample without EPS addition has an infrared spectrum at 1583 cm⁻¹. -1 The characteristic peak of glycolic acid appears at 1720 cm⁻¹. -1 An aldehyde intermediate peak appears at 1626 cm⁻¹. -1 The formate signal is weak at 1626 cm⁻¹, and bio2-Cu3P / Ni2P is at 1626 cm⁻¹. -1 A strong formate signal was observed at 1720 cm. -1 An aldehyde intermediate peak appears at 1583 cm⁻¹, while... -1 The glycolic acid signal almost disappeared, indicating that the reaction pathway of the Cu3P / Ni2P sample without EPS addition was mainly mediated by glycolic acid, while the reaction pathway of bio2-Cu3P / Ni2P was mainly mediated by glyoxal. The bio-anchored carbon and nitrogen fragments successfully switched the reaction pathway from the glycolic acid pathway to the glyoxal pathway.
[0067] Figure 13 In the diagram, a is a left view of the theoretical model structure of Cu3P / Ni2P in Comparative Example 3, b is a top view of the theoretical model structure of Cu3P / Ni2P in Comparative Example 3, c is a left view of the theoretical model structure of the sample in Example 1, and d is a top view of the theoretical model structure of the sample in Example 1. Figure 13 In diagram a, a heterojunction is formed by Cu3P(111) and Ni2P(210). Figure 13 b shows the carbon-nitrogen fragments introduced into the heterojunction interface via CP covalent bonds.
[0068] Figure 14 In Figure a, it is a schematic diagram of the two pathways of the ethylene glycol oxidation reaction; in Figure b, it is a free energy step diagram of the two pathways on bio2-Cu3P / Ni2P; and in Figure c, it is a free energy step diagram of the two pathways on Cu3P / Ni2P. Figure 14 The data in Figure c shows that the glycolic acid pathway (Pathway 1) has the lowest energy barrier (1.29 eV) on Cu3P / Ni2P, consistent with the glycolic acid signal in FTIR. Figure 14 As shown in Figure b, the glyoxal pathway (Pathway 2) has the lowest energy barrier (1.01 eV) on bio2-Cu3P / Ni2P, while the glycolic acid pathway energy barrier increases to 1.16 eV. The theoretical calculation results are in complete agreement with the experimental observations, confirming that the carbon-nitrogen fragment anchoring structure switches the reaction pathway from the glycolic acid pathway to the glyoxal pathway through electronic regulation, thereby achieving high formate selectivity.
[0069] Test Example 2 Preparation of PET hydrolysate: 2g of commercial PET microplastic particles, transparent PET beverage bottle fragments, and purple PET beverage bottle fragments were added to 50mL of 2mol / L KOH solution and hydrolyzed at 80℃ for 72h to obtain hydrolysate containing ethylene glycol and potassium terephthalate. This hydrolysate was used directly as the electrolyte. The Cu3P / Ni2P heterojunction electrocatalyst of Example 1 was used as the anode and Pt electrode as the cathode in an electrolytic cell.
[0070] Figure 15 Figure a shows the linear sweep voltammetry (LSV) curves in different PET hydrolysates in Test Example 2; figure b is a schematic diagram of the solar-driven PET upgrade and recycling coupled hydrogen production system; figure c is the FTIR spectrum of recovered terephthalic acid; and figure d is the FTIR spectrum of recovered potassium diformate. The results show that the polarization curves in the transparent bottle hydrolysate, purple bottle hydrolysate, and microplastic hydrolysate are basically identical to those in the pure ethylene glycol solution, at 100 mA / cm². 2 The potential deviation from that of pure ethylene glycol solution is no more than 2%, indicating that the catalyst of this invention has excellent tolerance to impurities in real plastic hydrolysate. Figure 15 Figure b is a schematic diagram of the solar-driven PET upgrade and recycling coupled hydrogen production system of the present invention, which directly connects the photovoltaic panel to the two-electrode electrolyzer. Figure 15In the image, c represents solid terephthalic acid obtained by acidifying and filtering the anolyte after electrolysis; its FTIR spectrum is consistent with that of the standard. Figure 15 In the figure, d represents potassium diformate solid obtained by concentrating and drying the filtrate. The FTIR spectrum is consistent with that of the standard. The results indicate that the catalyst of this invention can directly utilize solar energy to drive the upgrading and recycling of PET plastics, simultaneously producing hydrogen and recovering high-purity monomers.
[0071] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A Cu3P / Ni2P heterojunction electrocatalyst anchored by EPS-derived carbon and nitrogen fragments, characterized in that, The invention includes a conductive substrate and a Cu3P / Ni2P heterojunction nanoarray grown on the conductive substrate. Carbon and nitrogen fragments are anchored at the heterojunction interface of the Cu3P / Ni2P heterojunction nanoarray via CP covalent bonds. The carbon and nitrogen fragments are derived from bacterial extracellular polymers.
2. The Cu3P / Ni2P heterojunction electrocatalyst according to claim 1, characterized in that, The Cu3P / Ni2P heterojunction nanoarray is composed of three-dimensional nanoclusters, which are formed by stacking nanosheets with a thickness of 20~50nm.
3. The Cu3P / Ni2P heterojunction electrocatalyst according to claim 1, characterized in that, The intensity ratio of the D band to the G band in the Raman spectrum of the carbon-nitrogen fragment is I. D / I G The value is 0.8~1.
2.
4. The method for preparing the Cu3P / Ni2P heterojunction electrocatalyst according to any one of claims 1 to 3, characterized in that, Includes the following steps: Place the conductive substrate in a Cu-containing environment 2+ and Ni 2+ Electrodeposition was performed on an aqueous solution of bacterial extracellular polymer to obtain a conductive substrate with a Cu(OH)2 / Ni(OH)2 precursor nanoarray grown on it. The conductive substrate on which the Cu(OH)2 / Ni(OH)2 precursor nanoarray is grown is subjected to heat treatment with a phosphorus source to obtain the Cu3P / Ni2P heterojunction electrocatalyst.
5. The preparation method according to claim 4, characterized in that, The Cu-containing 2+ and Ni 2+ The volume fraction of bacterial extracellular polymers in the aqueous solution is 5-30%.
6. The preparation method according to claim 4 or 5, characterized in that, The Cu-containing 2+ and Ni 2+ Cu in bacterial extracellular polymeric aqueous solution 2+ Concentration of 1~5 mmol / L, Ni 2+ The concentration is 1~5 mmol / L.
7. The preparation method according to claim 4, characterized in that, The electrodeposition treatment is performed at a potential of -1.5 to -1.0 V vs. Ag / AgCl, and the electrodeposition treatment time is 100 to 500 s.
8. The preparation method according to claim 4, characterized in that, The phosphorus source includes one or more of sodium hypophosphite, sodium phosphite, and sodium phosphate; the mass ratio of the phosphorus source to the Cu(OH)2 / Ni(OH)2 precursor nanoarray in the conductive substrate on which the Cu(OH)2 / Ni(OH)2 precursor nanoarray is grown is 1:1 to 5:
1.
9. The preparation method according to claim 4, characterized in that, The heat treatment temperature is 300~400℃, and the holding time is 1~4h.
10. The application of the Cu3P / Ni2P heterojunction electrocatalyst according to any one of claims 1 to 3 or the Cu3P / Ni2P heterojunction electrocatalyst prepared by the preparation method according to any one of claims 4 to 9 in the coupled hydrogen production from PET plastic upgrading and recycling, characterized in that, The Cu3P / Ni2P heterojunction electrocatalyst serves as the anode and / or cathode.
Citation Information
Patent Citations
Microbial agent for improving rocky desertification soil in karst trough valley region as well as preparation and application of microbial agent
CN112940964A
